Penerapan Model TAI untuk Meningkatkan Kemampuan Kerjasama dan Hasil Belajar Matematika Materi Barisan dan Deret Kelas IXC SMP Negeri 4 Sumbang Semester 2 Tahun Pelajaran 2017/2018 - Theresia Warsini (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2019)
The problem that underlies this research is the lack of collaboration and mathematics learning outcomes of students of class IX C of SMP N 4 Sumbang. This can be seen if students have difficulty in understanding the material, students tend to be quiet and do not want to cooperate with friends, even though the cooperation of students is very necessary to achieve the success of teaching and learning. To create student cooperation in the learning process, a learning model is needed. One such learning model is the TAI (Teams Assisted Individualization) type of cooperative learning model, where the model is oriented towards collaboration, both mentally, attitudes, and socially. The purpose of this research is to find out the improvement of cooperation and learning outcomes in mathematics through the application of cooperative learning models in the form of sequence and series TAI material. This research is a Classroom Action Research. Learning tools, namely syllabus, lesson plans, teaching materials, and worksheets. While the research instrument is the description test and observation sheet. The subjects of the study were 22 students of the IXC class at SMPN 4 Sumbang. Data sources come from teachers and students. Data collection techniques are by observation, and tests. The study was conducted in December 2017 until April 2018. The subject and time of the study were chosen because the researcher taught in the class and the implementation time was adjusted to the lesson schedule. The research procedure begins with problem identification, action planning, implementation of actions and observations, and analysis and reflection. The results showed that the ability of student cooperation, from the first cycle the percentage of student cooperation with the category of